Fluctuating fortunes of a collective entreprise: The case of the Agroforestry Tree Seeds Association of Lantapan (ATSAL) in the Philippines - Catacutan, Delia; Bertomeu, Manuel; Arbes, Lyndon; Duque, Caroline; Butra, Novie (International Food Policy Research Institute, 2008)
The Agroforestry Tree Seeds Association of Lantapan (ATSAL) in Bukidnon province, southern Philippines was organized in 1998, facilitated by the World Agroforestry Centre (ICRAF). Farmers were trained on germplasm collection, processing and marketing of agroforestry tree seeds and seedlings. ATSAL has been marketing various tree seeds and seedlings with apparent success, and has provided training on seed collection and nursery management to farmers, government technicians, and workers from non-government organizations (NGOs). This paper reports on the initial results of an on-going study to assess the effectiveness of ATSAL's marketing strategy, including group dynamics, and the issues and challenges the group faces. It was found that during the first two years, ATSAL's market share of greatly demanded timber tree species increased significantly, thus helping to disseminate widely these important species among farmers. ICRAF's technical back-up was an advantage, increasing the Association's market credibility. Subsequently, ATSAL extended its market to the central Philippines, but failed to meet the demand for seeds due to organizational limitations. Market competition exists, where a nonmember was able to take a larger market share than was the group. Nonetheless, ATSAL has established its name as a viable community-based seed and seedling producer, maintaining a stronghold in local and regional markets. Collective action is important for smallholders to break in, and gain market access, but is unlikely to sustain without effective leadership and some facilitation (in some cases even ongoing), thus requiring expenditures on repairs and maintenance through continuous technical and leadership training for the collective, and technical back-up and facilitation by an intermediary. Finally, facilitating smallholder collective action is essentially an arduous task, requiring the supporting agency to hold a firm grasp of market realities, to invest in the maintenance of collective action, to provide continuous technical back-up, and to ascertain the conditions that make collective action succeed.